Implementation of the Quizizz-Based ASSURE Learning Model in Islamic Religious Education - Gasmi, Nur; Afifah, Umi; Kasturi, Rima; Ananda, Rizki; Tadjuddin, Nilawati (Faculty of Education and Teacher Training, Islamic State University of Kiai Haji Achmad Siddiq Jember, 2025)
Technology and information in the world of education play a crucial role in improving the effectiveness of the learning process. Therefore, teachers are required to continue to develop their teaching skills and integrate technology into learning activities. This study aims to analyze teacher strategies in designing effective and efficient learning in accordance with technological developments. The method used is descriptive qualitative with a focus on the implementation of the ASSURE learning model based on Quizizz in Islamic Religious Education subjects at SMPN 1 Buay Bahuga. The results of the study showed that the implementation of this model significantly improved students' learning experiences. With the active involvement of students, the ASSURE learning model based on Quizizz has been proven to be able to improve learning outcomes and create a more varied and enjoyable learning atmosphere.